Pterostichus (Anilloferonia) diana LaBonte (Coleoptera: Carabidae: Pterostichini), a replacement name for P. (A.) lanei (Hatch, 1935), and validity and redescription of P. (A.) malkini (Hatch, 1953) - Labonte, James R. (Zootaxa, 2013)
A replacement name for Pterostichus (Anilloferonia) lanei (Hatch), 1935, is necessary because P. lanei (Hatch) is a sec-ondary homonym of P. (Pseudoferonina) lanei Van Dyke, 1925. I have selected P. (A.) diana as this replacement name. Pterostichus (Anilloferonia) malkini (Hatch), 1953, was described from a single female collected in 1951. Since then five more specimens have been collected, including males. Based on this additional material it is clear this species is valid, which had been uncertain. Since the original description of P. malkini did not include male characteristics, several of which are diagnostic, a detailed description of this species is provided. Locality and habitat details for this rarely collected species are included. Characters differentiating P. malkini from the other species of P. (Anilloferonia) are illustrated and discussed.